From Words to Violence: Tracing the Trajectory of Dangerous Speech and Its Impact on the Ahmadiyya Community in Bangladesh - Md. Akmal Hossain; Muhammad Mahmudur Rahman (Universitas Islam Internasional Indonesia (UIII), 2025)
This study seeks to examine the phenomenon of 'dangerous speech' and its connection to the violent acts perpetrated against the Ahmadiyya Community in Bangladesh. The Ahmadiyya Community, also called the Qadiani Movement, originated in the late 19th century in the Indian subcontinent and later expanded to Bangladesh in 1912. Despite this, Islamic clerics and many prominent political figures in Bangladesh adamantly refuse to recognize Qadianis as Muslims. This refusal has sparked riots, political violence, divisions, and electoral maneuvering in Bangladesh. This research employs the